Le geometrie del disfacimento umano nel Bellum civile di Lucano: per una lettura della battaglia di Marsiglia - Bocchi, Giuseppe (Polskie Towarzystwo Filologiczne, 2021)
Lucan describes the naval battle of Massilia in Bellum Civile III 538–762 through sequences which only apparently seem to have no structure: indeed, the poet combines scenes where the soldiers (or groups of soldiers) are either transfixed or amputee or drown into the sea (and more than one situation sometimes occurs to a single victim or group), and every sequence reworks this pattern in a terrifying crescendo of gruesome pictures. In doing so, this poet who has such a contentious relationship with Stoic philosophy identifies the bodies’ dismemberment with Rome’s general fall, corresponding to the crush of the universal logos from which all the calamities derive. Moreover, the destruction of both bodies and Roman civilisation is expressed through the intelligent use of rhetorical figures such as hyperbaton, enjambment, and chiasmus (or better, chiastic nuance). Separating the words and modifying the logical train of thought underscore that the world and the word undergo the same law of crumbling.